Evaluasi Program Ketahanan Pangan di Desa Gunung Jambat Kecamatan Suak Midai Kabupaten Natuna - Etia Tri Nurhidayah; Afrizal Afrizal; Kustiawan Kustiawan (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
The Food Security Program through the provision of broiler seeds in Gunung Jambat Village is carried out with the aim of increasing food availability and community welfare through the use of Village Funds. The realization of the 2023 budget reached 96%, but the implementation results were not optimal, as shown by the harvest success rate of only 54.05% of the 2,000 seedlings distributed. This study aims to evaluate the implementation of the program using the CIPP (Context, Input, Process, Product) evaluation model proposed by Stufflebeam & Coryn. The research method is qualitative with a descriptive approach, using interview, observation, documentation, and literature study techniques. The results of the study show that in terms of context, the program is in accordance with the needs of the community and government policies. In terms of inputs, the budget is adequate, but the facilities, infrastructure, and technical capacity of assistance are still limited. In terms of the process, the distribution of aid is going according to plan, but monitoring and coaching are not optimal. In terms of product, the achievement has not been in line with the goals due to the high chicken mortality rate and low crop yields, so that the benefits of sustainable economy have not been achieved. In conclusion, the implementation of the program is not optimal and requires improvements in planning, capacity building of human resources, technical assistance, market analysis, and supervision so that the program's objectives can be achieved effectively.